Effects of a 16-Week Training Program with a Pyramidal Intensity Distribution on Recreational Male Cyclists - Magalhães, Pedro M.; Cipriano, Flávio; Morais, Jorge E.; Bragada, José A. (Sports (Basel), 2024)
Different training intensity distributions (TIDs) have been proposed to improve cycling performance, especially for high-competition athletes. The objectives of this study were to analyze the effect of a 16-week pyramidal training intensity distribution on somatic and power variables in recreational cyclists and to explore the training zone with the greatest impact on performance improvement. The sample consisted of 14 male recreational cyclists aged 41.00 ± 7.29 years of age. A number of somatic variables were measured. During an incremental protocol, power at a 4 mMol·L−1 blood lactate concentration (P4), corresponding power to body mass ratio (P/W P4), and heart rate (HR P4) were also measured. Among the somatic variables, the percentage of fat mass showed the greatest improvement between moments (p < 0.001, d = 0.52). Both P4 (p < 0.001, d = 1.21) and P/W P4 (p < 0.001, d = 1.54) presented a significant increase between moments. The relative improvement in P4 (% P4) showed a significant correlation (Rs = 0.661, p = 0.038) and relationship (R2 = 0.61, p = 0.008) mainly with training zone Z2 (blood lactate levels ≥ 2 and <4 mMol·L−1). It seems that spending more time in Z2 promoted an improvement in both somatic and power variables in recreational cyclists.